1976
DOI: 10.1111/j.1469-7610.1976.tb00391.x
|View full text |Cite
|
Sign up to set email alerts
|

An Observation Scheme for Recordingchildren's Imaginative Doll Play

Abstract: Summary A methodology for recording and quantifying children's imaginative doll play was evaluated with a group of 10 normal children, aged 18–42 months and a group of 9 ESNS children, aged 57–103 months. With both groups there was high inter‐rater reliability and the measures used to quantify the play showed an expected positive correlation with Developmental Age. Furthermore the measures were sensitive to changes in the play brought about by different play materials and experimenter modelled doll play.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 3 publications
4
30
0
3
Order By: Relevance
“…With development, children are able to use less realistic objects as the motor for their play as they become able to transform them into imaginative objects that fit their play scenario [47,48]. For example, children begin to pick up blocks and hold them to the ear to listen to imaginary phone conversations.…”
Section: Analyses Of the Children's Discoursementioning
confidence: 99%
“…With development, children are able to use less realistic objects as the motor for their play as they become able to transform them into imaginative objects that fit their play scenario [47,48]. For example, children begin to pick up blocks and hold them to the ear to listen to imaginary phone conversations.…”
Section: Analyses Of the Children's Discoursementioning
confidence: 99%
“…Other studies have examined the impact of realistic versus non-realistic toys on symbolic behaviours in children's play (Jeffree & McConkey, 1976;McLoyd, 1983;Pulaski, 1973;Trawick-Smith, 1990, 1993. In these studies, panels of adults were first interviewed to select toys that could be categorised as realistic -that is, replicas J. of real objects that suggest obvious make-believe uses (e.g.…”
Section: Realistic Versus Non-realistic Toysmentioning
confidence: 98%
“…While children between 1V2 and about 4 years of age do show an increasing capacity for pretending with dissimilar objects, or no object at all, it does not necessarily follow that they will prefer to play with such objects or show more frequent pretend when they do play with them. 210 JOURNAL OF GENETIC PSYCHOLOGY Two-and 3-year-olds have been found to show more imaginative play with realistic than with unstructured toys (5,6), but this is not surprising since it is not until about age three that children become capable of pretending with unstructured toys. Studies of children between three and seven years of age have not demonstrated greater amounts of pretend play with unstructured than with realistic objects, but they have shown that unstructured play materials produce a greater variety of fantasy themes (8,9,10).…”
Section: A Introductionmentioning
confidence: 93%
“…While younger preschool children have been found to spend more time playing with realistic than unstructured toys (5), an older group showed no difference in time spent playing with toys of different structure levels (to). In one study, only "high fantasy" 5-to 7-year-olds preferred playing with unstructured toys; "low fantasy" children preferred realistic toys (9).…”
Section: A Introductionmentioning
confidence: 98%